Microbial solubilization of phosphate, potassium rocks and their effect on khella (Ammi visnaga) growth - Hassan, E. A.; Hassan, Enas A.; Hamad, El. H. (2010)
Biofertilizers have been used as sources to improve plant nutrients in sustainable agriculture Experiments were conducted to evaluate the potential of several phosphate solubilizing bacteria (PSB) Bacillus megaledum and potassium solubilizing bacteria (KSB) Bacillus circulans to solubilize tricalcium phosphate (TCP).
Includes reference.
Summary in Arabic.
1
Keywords: Bacillus megaterium; Enterobacter cloacae; Phosphate rock; Feldspar; Solubilization; Bishop's-weed .